Perubahan Fungsi Ventrikel Kiri pada Penderita HIV - Anggia Chairuddin Lubis; Abdullah Afif Siregar; Sutomo Kasiman (Jurnal Kardiologi Indonesia, 2012)
Background. Patients with HIV have increased risk for myocardial dysfunction but the underlying mechanisms remain unknown.Methods & Results. This study evaluated noninvasively ventricular function in HIV infected patients with no clinical evidence of cardiovascular disease, with determination of left ventricular systolic and diastolic function, as well as measurement of CD 4. Between November 2009 and June 2010, 22 patients agreed to participate in a follow up study. All patients had normal LVEF and FS at both examinations. There was no evidence for a relationship between LVEF changes and either CD 4 changes, CD 4 nadir and HIV stadium. However an increase in mean EPSS was observed at follow up (p=0.045) and associated with lower CD 4 cell counts. At the initial visit, 1 patient had left ventricular dysfunction, and 4 patients at follow up. All patients had normal TAPSE values at both examinations.Conclusion. HIV related cardiomyopathy appears not to constitute a problem in HAART era. However subclinical cardiac abnormalities are frequently observed. The usefulness of systematic noninvasive screening in this population should be considered.